The black book of colors - Cottin, Menena (Groundwood Books/House of Anansi Press, 2008)
This title invites readers to imagine living without sight through remarkable illustrations done with raised lines and descriptions of colors based on imagery. Braille letters accompany the illustrations and a full Braille alphabet offers sighted readers help reading along with their fingers.